Beneficial effects of simvastatin in wound healing: review of the literature - Chandra Wijaya Setiawan; Luh Made Mas Rusyanti; Marrietta Sugiarti Sadeli (Bali Dermatology Venereology and Aesthetic Journal, 2022)
Wound healing is a complex, natural biological, and dynamic process or loss of cellular structures, tissue layers, and replacing damaged tissue. Molecular responses, cellular components, and humoral components are healing process that occurs in hemostasis, including inflammation, proliferation, and remodeling. In order to achieve good healing, these four steps must be performed in the right order and at the right time. In recent years, research has shown that simvastatin has pleiotropic properties that have been linked to improved wound healing in experimental animals and humans. However, higher-quality and evidence-based research is needed to determine the duration of treatment, the best method of administration, the correct dose, and to relate the pleiotropic properties of simvastatin to its potential therapeutic.